Renewable energy and climate change - Quaschning, Volker 1969- (Wiley India, 2010)
This dazzling introductory textbook encompasses the full range of today's important renewable energy technologies. Solar thermal, photovoltaic, wind, hydro, biomass and geothermal energy receive balanced treatment with one exciting and informative chapter devoted to each. As well as a complete overview of these state-of-the-art technologies, the chapters provide: clear analysis on their development potentials; an evaluation of the economic aspects involved; concrete guidance for practical implementation; advice on how to reduce your own energy waste.